Rationality and the Jordan–Gatti–Viniberghi Decomposition. Issue 1 (14th March 2014) - Levy, Jason
Abstract: We verify our earlier conjecture and use it to prove that the semisimple parts of the rational Jordan–Kac–Vinberg decompositions of a rational vector all lie in a single rational orbit.